2013
DOI: 10.1093/cercor/bhs401
|View full text |Cite
|
Sign up to set email alerts
|

Common Variants in Psychiatric Risk Genes Predict Brain Structure at Birth

Abstract: Studies in adolescents and adults have demonstrated that polymorphisms in putative psychiatric risk genes are associated with differences in brain structure, but cannot address when in development these relationships arise. To determine if common genetic variants in disrupted-in-schizophrenia-1 (DISC1; rs821616 and rs6675281), catechol-O-methyltransferase (COMT; rs4680), neuregulin 1 (NRG1; rs35753505 and rs6994992), apolipoprotein E (APOE; ε3ε4 vs. ε3ε3), estrogen receptor alpha (ESR1; rs9340799 and rs2234693… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
116
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 129 publications
11
116
0
1
Order By: Relevance
“…5 However, larger cortical areas in our e3e4 children resemble larger parietal volumes in e3e4 infants (ages 8.5-14 months) 7 relative to e3e3 participants. Moreover, consistent with our results, prior studies found similar IQ or cognitive performance between e3e4 and e3e3 children.…”
Section: Brain Regions With Apoe E-by-age Interactions Are Shown (Grementioning
confidence: 67%
See 4 more Smart Citations
“…5 However, larger cortical areas in our e3e4 children resemble larger parietal volumes in e3e4 infants (ages 8.5-14 months) 7 relative to e3e3 participants. Moreover, consistent with our results, prior studies found similar IQ or cognitive performance between e3e4 and e3e3 children.…”
Section: Brain Regions With Apoe E-by-age Interactions Are Shown (Grementioning
confidence: 67%
“…[1][2][3][4] In addition, APOE e4 may influence brain development. [5][6][7] However, the APOE e4 allele demonstrates antagonistic pleiotropy, with deleterious effects on cognition, brain morphometry, and activation primarily after 55 years of age, but no negative 8 or even beneficial effects in adults younger than 50 years 9,10 and children aged 6 to 15 years. [11][12][13] Compared to non-e4 carriers, healthy children carrying e4 (8-20 years) tended to have thinner entorhinal cortex, 5 while healthy infants carrying e4 showed altered brain measures in regions affected by AD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations